Rediseño de la malla curricular de la carrera de Secretariado Ejecutivo del ITS. Ismael Pérez Pazmiño de Machala en correspondencia al mercado laboral. - Ramírez Aguilar, Ana Paola (2017)
The purpose of this research is; To study and redesign the Curricular Matrix of the Technology Career in the Executive Secretariat of the Ismael Pérez Pazmiño Higher Technological Institute of the city of Machala, in order to improve student training processes, with a new scientific vision in the disturbing political panorama, Economic and social life that devastates the lives of citizens in this changing and unequal digital era, which our country shows in the second decade of the twenty-first century. This study showed the low relevance of the current mesh of the race, facing the problems of the zonal context, the incoherence with the objectives of good living and change of the productive matrix. The theoretical support of this work proposes a new epistemic horizon according to the guidelines of the ESC. The type of research is Quantitative-qualitative was used surveys to the students and entrepreneurs of the province of El Oro, interviews to teachers, professionals and graduates of the race with the purpose of validating the professional profile and propose a mesh according to technological changes, Environmental and intercultural.